The Release of Inflammatory Mediators from Acid-Stimulated Mesenchymal Stromal Cells Favours Tumour Invasiveness and Metastasis in Osteosarcoma - Sofia Avnet (MDPI AG, 2021)
Osteosarcoma is the most frequent primary malignant bone tumour with an impressive tendency to metastasise. Highly proliferative tumour cells release a remarkable amount of protons into the extracellular space that activates the NF-kB inflammatory pathway in adjacent stromal cells. In this study, we further validated the correlation between tumour glycolysis/acidosis and its role in metastases. In patients, at diagnosis, we found high circulating levels of inflammatory mediators (IL6, IL8 and miR-136-5p-containing extracellular vesicles). IL6 serum levels significantly correlated with disease-free survival and 18F-FDG PET/CT uptake, an indirect measurement of tumour glycolysis and, hence, of acidosis. In vivo subcutaneous and orthotopic models, co-injected with mesenchymal stromal (MSC) and osteosarcoma cells, formed an acidic tumour microenvironment (mean pH 6.86, as assessed by in vivo MRI-CEST pH imaging). In these xenografts, we enlightened the expression of both IL6 and the NF-kB complex subunit in stromal cells infiltrating the tumour acidic area. The co-injection with MSC also significantly increased lung metastases. Finally, by using 3D microfluidic models, we directly showed the promotion of osteosarcoma invasiveness by acidosis via IL6 and MSC. In conclusion, osteosarcoma-associated MSC react to intratumoural acidosis by triggering an inflammatory response that, in turn, promotes tumour invasiveness at the primary site toward metastasis development.